PERBEDAAN PENGARUH CARA MEMEGANG TURBO TERHADAP PRESTASILEMPAR TURBO PADA SISWASDN SEMANTUN DI KECAMATAN PERMATA KECUBUNG KABUPATEN SUKAMARA TAHUN 2015 - Putra, Roma NSH (Jurnal Aplikasi Manajemen Pendidikan, 2015)
This research aimed to determine differences in the effects of exercise by holding the turbo between the hold using the five fingers and hold to use three fingers in the middle of the turbo, behind turbo, and behind the turbo with the index finger on the tail of the achievements of throwing a turbo on the students of SDN SemantunSukamara year 2015, and to know how to hold the turbo Which best to improve performance in throwing turbo. This research used an experimental method with the student population of SDN Semantun class IV, V, and VI of the academic year 2014/2015 amounted to 86 students, divided into five classes. The sampling technique in this study using total sampling or total population. Data collection techniques is to use the test and measurement capabilities turbo sheet, which is then divided into two groups using ordinal pairing where each treatment group received three different exercises. Data analysis techniques in this study using paired sample T-test and independent sample t-test. The result are: (1) there is a significant difference between holding turbo turbo in the middle, behind the turbo and turbo with the index finger behind at the tail of the turbo throw achievement; (2) how to hold the turbo behind the turbo with the index finger on the tail least better than holding the turbo in the middle or back of the turbo to turbo throwing achievement; (3) there is no difference between the effect of turbo holding with three fingers and five toes on turbo throw achievement.